Pengaruh motivasi dalam proses pembangunan diri remaja menurut persepktif Islam: Kajian di Pusat Motivasi Aliran Pelajar, Kuala Lumpur / Nur Shahidah Pa'ad - Nur Shahidah, Pa'ad (2017)
The implementation of this study stems from a major issue of the decline in motivation suffered by adolescents after some time out of motivation program. This has often been questioned, and whether Islamic motivation programs have also experienced the same problem. Based on the survey of the literature, several matters have been identified as the reasons which contribute to the deterioration in motivation. The gap left by previous studies in discussing this issue warrants further research. Therefore, the present study aims to unravel the issue in greater depth, solve existing problems and provide the best solution. Using a qualitative approach, the study has selected case studies as its research design in examining five cases of adolescents who have participated in the Motivasi Alihan Pelajar (MAP) program. In order to explore the reality of the effect of motivation in the process of self-development of the five informants, data were collected through in-depth interviews, participants’ observation, document analysis and additional interviews with the program regular coach. The theoretical thematic analysis which involves several stages was applied as the analysis method. The results reveal that the effect of self-motivation in the development of informants is a complex process involving various elements relating to the informants and elements that exist in their social context. Awareness to improve themselves and the need for certain skills has encouraged the formation of self-development commitment by the informants while in the program. However, maturity and opportunities to develop themselves have determined the extent that commitment can be implemented. Accordingly, through this study, the reality of the formation of self-development motivation of the informants is highlighted and suitable Islamic motivation model are suggested.